Anthropogenic Noise Aggravates the Toxicity of Cadmium on Some Physiological Characteristics of the Blood Clam Tegillarca granosa - Shi, Wei; Han, Yu; Guan, Xiaofan; Rong, Jiahuan; Du, Xueying; Zha, Shanjie; Tang, Yu; Liu, Guangxu (Frontiers in Physiology, 2019)
Widespread applications of cadmium (Cd) in various products have caused Cd contamination in marine ecosystems. Meanwhile, human activities in the ocean have also generated an increasing amount of noise in recent decades. Although anthropogenic noise and Cd contaminants could be present simultaneously in realistic marine environments, the physiological responses of marine bivalve mollusks upon coexposure to anthropogenic noise and toxic metal contaminants, including Cd remain unclear. Therefore, the combined effects of anthropogenic noise and Cd on the physiological responses of the blood clam Tegillarca granosa were investigated in this study. The results showed that 10 days of coexposure to anthropogenic noise and Cd can enhance adverse impacts on metabolic processes, as indicated by the clearance rate, respiration rate, ammonium excretion rate, and O:N ratio of T. granosa. In addition, both the ATP content, ATP synthase activity and genes encoding important enzymes in ATP synthesis significantly declined after coexposures to anthropogenic noise and Cd, which have resulted from reduced feeding activity and respiration. Furthermore, the suppressed activity of AChE and downregulated neurotransmitter-related genes were observed after coexposure to anthropogenic noise and Cd, which suggests an enhanced neurotoxicity under coexposure. In conclusion, our study demonstrated that anthropogenic noise and Cd would have synergetic effects on the feeding activity, metabolism, and ATP synthesis of T. granosa, which may be due to the add-on of stress responses and neurotransmitter disturbances.